Pengaruh Kepemimpinan Tranformasional, Disiplin Kerja, Kompetensi Terhadap Kinerja Koordinator Statistik Kecamatan Di Lingkungan BPS Provinsi Banten. - Fajar Sidik Karimulloh; Dadan Ramdani; Subarji Subarji; Syahroni Syahroni (E-Journal Studia Manajemen, 2022)
This research aims to identify factors that can explain the employee performance of the District Statistics Coordinator at the District / City BPS in Banten Province. The study focused on the effects of leadership, work discipline, and competency on employee performance. The research method employs a quantitative survey with 80 samples drawn from the District Statistics Coordinator's staff. A fascinating discovery from this study is the partial and simultaneous effect of the predictor variables when the R Square value is zero point five hundred sixty-nine. It may be deduced that the combined influence of leadership, work discipline, and competency on employee performance is 56%. At the same time, the rest are factors that are not covered by this research paradigm. These findings suggest that, at least in part, leadership, work discipline, and competency can be employed as predictor variables for employee success. These findings' consequences and recommendations are explored to enhance both academic and practical human resource management..